Anemia Control in Kidney Transplant Recipients Using Once-Monthly Continuous Erythropoietin Receptor Activator: A Prospective, Observational Study - Klemens Budde; Thomas Rath; Volker Kliem (Journal of Transplantation)
In a multicenter, prospective, observational study of 279 kidney transplant recipients with anemia, the efficacy and safety of once-monthly continuous erythropoietin receptor activator (C.E.R.A.) were assessed to a maximum of 15 months. The main efficacy variable was the proportion of patients achieving a hemoglobin level of 11-12 g/dL at each of visits between months 7 and 9. At study entry, 224 patients (80.3%) were receiving erythropoiesis stimulating agent (ESA) therapy including darbepoetin alfa (98), epoetin beta (61), and C.E.R.A. (45). The mean (SD) time between C.E.R.A. applications was 34.0 (11.9) days. Among 193 patients for whom efficacy data were available, mean (SD) hemoglobin was 11.1 (0.99) g/dL at study entry, 11.5 (1.1) g/dL at month 7, 11.6 (1.3) g/dL at month 9, and 11.4 (1.1) g/dL at month 15. During months 7–9, 20.7% of patients had all hemoglobin values within the range 11-12 g/dL and 64.8% were within 10–13 g/dL. Seven patients (2.5%) discontinued C.E.R.A. due to adverse events or serious adverse events. In this observational trial under real-life conditions, once-monthly C.E.R.A. therapy achieved stable hemoglobin levels in stable kidney transplant recipients with good tolerability, and with no requirement for any dose change in 43% of patients.